Effect of FYM and gypsum on growth and yield attributing traits on radish (Raphanus sativus) using RSC water (Current Horticulture, 2024)
The response of treatments comprising three levels each of farmyard manure (0, 10 and 20 tonnes/ha) and gypsum (0, 50 and 100% neutralization of RSC) were laid out in a factorial RBD with three replications in a net plot of 3.0 m × 3.0 m at Research Farm of the Department of Vegetable Science, CCS Haryana Agricultural University, Hisar, during 2017-18 and 2018-19. The application of farmyard manure and gypsum individually and in combination significantly influenced growth, yield traits and seed yield of radish (Raphanus sativus L.) cultivar Punjab Safed. Among the interaction combinations, plant height at harvesting, number of pods/plant, pod weight, pod length, number of seeds/pod, seed recovery (%), seed yield (g/plot), seed yield (kg/ha), biological yield (q/ha) and harvest index (%) were significantly maximum in F2G2 treatment, where, farmyard manure was applied at the rate of 20 tonnes/ha in combination with 100% neutralization of RSC by gypsum during both the years.
Keywords: FYM; Gypsum; RSC water; Seed yield; Yield traits